KENASABAN FIBRINOGEN PLASMA DENGAN PENEBALAN ARTERI INTIMA-MEDIA KAROTIS KOMUNIS DI DIABETES MELITUS (Correlation Plasma Fibrinogen With Intima-Media Thickness of Carotid Artery in Diabetes Mellitus) - Dwi Aryani; Budi Mulyono; Osman Sianipar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Diabetes mellitus is a global problem due to the increase of its prevalence, morbidity and mortality. Diabetes mellitus has chroniccomplications such as : micro vascular and macro vascular. The macro vascular complications reveal as atherosclerosis. The increase ofcarotid communist IMT was examined by using USG, which has become the standard for assessing atherosclerosis and recommended by theAmerican Heart Association. Fibrinogen levels have a role in atherosclerosis. This study was design cross-sectionals to know the associationbetween plasma fibrinogen with carotid communist IMT in patients with DM by special examination. The subjects were patients with DMcoming to Dr DR. Sardjito Yogyakarta and fulfil the inclusion as well as the exclusion criteria. The examination of fibrinogen was carried out by Claus’s method. The result showed positive correlation between plasma fibrinogen with carotid communist IMT in type 2 diabetes mellitus, r = 0.36 and p = 0.021. There is also positive correlation between age and carotid IMT with r = 0.314 and p = 0.048.